Temporalities in tension: chemsex and the critique of normative time in the play El Gé (Palimpsesto, 2025)
This article analyses the discourses of temporality embedded in the play El Gé, which addresses the phenomenon of chemsex in Madrid, Spain. Our aim is to examine how these discourses challenge and reconfigure temporal dynamics. We interrogate the relationship between the temporalities experienced during chemsex encounters and the external temporal structures that frame them. Employing Critical Discourse Analysis, we explore how the play enacts a critique of normative temporal regimes. From the script, we identify a dual discourse: on the one hand, the play questions hegemonic temporalities associated with productivity and alienation; on the other, it reveals how chemsex practices may inadvertently reproduce the cyclical logics of those same temporal structures.
Keywords: temporality; chemsex; critical discourse analysis; normative temporality; theatre analysis